Eocene-Oligocene paleoenvironmental changes in the South Orkney Microcontinent (Antarctica) linked to the opening of Powell Basin - López-Quirós, Adrián; Escutia, Carlota; Etourneau, Johan; Rodríguez-Tovar, Francisco J.; Roignant, Sabine; Lobo, Francisco J.; Thompson, Alasdair (Nick); Bijl, Peter K.; Bohoyo, Fernando; Salzmann, Ulrich; Evangelinos, Dimitris; Salabarnada, Ariadna; et al. (Global and Planetary Change, 2021)
The scarcity of paleo-records from the Antarctic Peninsular region of the Southern Ocean hinders our understanding of the timing of the opening of Drake Passage, specifically in the region of the South Orkney Microcontinent (SOM) and Powell Basin, between the Scotia and Antarctic plates. At Ocean Drilling Program (ODP) Hole 696B, SOM sediments recovered from the upper Eocene-lower Oligocene (~37.6–32.2 Ma) enable us to gain insight into paleoceanographic and paleoclimatic changes during gateway opening across the major Cenozoic climate shift —the Eocene-Oligocene transition— when the Antarctic ice sheet first reached sea-level. We propose the following sequence of events, based on a multi-proxy analysis of sediment facies, mineralogy, and organic matter geochemistry (TOC, TN, C/N ratio, δ13C, δ15N, and n-alkanes). During the late Eocene (~37.6–35.5 Ma) the SOM was attached to the Antarctic Peninsula, and terrigenous sediments of likely local origin were deposited in shallow waters under conditions of reduced‑oxygen/low-salinity, and temperate climate. In the latest Eocene (~35.5–34.1 Ma), terrigenous input was reduced due to the separation of the SOM from the Antarctic Peninsula by proto-Powell Basin opening. Decreased sediment supply during continuous deepening of the SOM led to deposition of a condensed section with significant glauconitization, recurrent winnowing by bottom currents, and suboxic conditions near the sediment-water interface. At the time of the Eocene-Oligocene transition (EOT; ~34.1–33.6 Ma) two upward-coarsening sediment sections were deposited within an overall upward-fining section, which we interpret as records of regressive phases due to ice sheet expansion. During the early Oligocene (~33.6–33.2 Ma) the SOM deepened further because of continued opening of Powell Basin, and organic-rich sediments were deposited as a result of enhanced biological production, partially driven by enhanced upwelling. Major cooling caused a change from forests indicating relatively humid temperate conditions ...